Cavity‐Induced Enhancement of Magneto‐Optic Effects in Monolayer Transition Metal Dichalcogenides. Issue 7 (12th February 2018) - Da, Haixia; Gao, Lei; An, Yipeng; Zhang, Haiyan; Yan, Xiaohong
Abstract: Monolayer transition metal dichalcogenides represent a class of 2D direct‐bandgap semiconductors, which do not support magneto‐optical (MO) effects in the absence of magnetic field due to time reversal symmetry. Magnetic exchange field (MEF) has been demonstrated to be able to generate MO effects in monolayer transition metal dichalcogenides, causing Faraday rotation of several tenths of degree without the need of magnetic field. Here, the possibility of enhancing the MO effects of monolayer transition metal dichalcogenides upon MEF using a cavity structure is investigated. It is identified that the Faraday rotation (FR) angle can be boosted by choosing the proper thickness of optical cavity due to its resonant characteristics. In particular, unlike the conventional bulky magnetic materials always with fixed MO effects, the FR angle here can be manipulated by the chemical potential, enabling a route of engineering the MO effects in monolayer transition metal dichalcogenides. The results suggest 2D layered semiconductors being the possible building blocks in nonreciprocal MO devices. Abstract : The strategy of using a photonic cavity with monolayer transition metal dichalcogenide (TMDC) upon the application of magnetic exchange field for generating a giant Faraday rotation angle, which effectively enhances the performance of magneto‐optical effects and opens up an unprecedented way for tunable TMDC‐based magneto‐photonic devices, is proposed and demonstrated.